Influence of Pin Surface Hardness and Roughness on the Silent Chain Wear Resistance - Jin Lijun; Wang Qinglei; Jin Yumo; Fu Zhenming (Jixie chuandong)
The influence laws of pin surface hardness and roughness on the silent chain wear resistance is proposed,the relationship between the pin surface hardness,surface roughness and the silent chain wear resistance is expounded. The experiment results show that increasing the pin surface hardness,reducing the pin surface roughness,the silent chain wear resistance can be obviously improved,such measure is very efficient to the improvement of silent chain wear resistance.